Assessment in Kindergarten and First Grade of Primary School: A Comparative Perspective - Νικήτα Χριστίνα; Λαζαράκου Ελισάβετ; Μαλαφάντης Κωνσταντίνος; Τσώλη Κωνσταντίνα (Education Sciences, 2025)
The study focuses on the one hand on the examination of the methods used by teachers for the assessment of their students in the kindergarten and the 1st grade of the primary school and on the other hand on the highlighting of their perceptions regarding the assessment in these two classes as well as on the identification of the factors which lead to the differentiation of these perceptions. The research adopts the quantitative methodology using a questionnaire based on the Teacher Formative Assessment Practice Scale of Yan & Pastore (2022). The sample of the research was 127 teachers, 65 of whom were teachers with experience in the 1st grade in the last five years and the remaining 62 were kindergarten teachers. The research showed that teachers and kindergarten teachers differ in terms of the applied assessment techniques. Both apply formative assessment principles and inclusive practices with preschool teachers leading the way. The research seeks to enrich the knowledge about the factors that hinder the smooth transition of children from kindergarten to the 1st grade of primary school.